2005
DOI: 10.1108/09649420510591834
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of and about women as managers: investigating job involvement, self‐esteem and attitudes

Abstract: PurposeTo investigate specific barriers that might be hindering Maltese women from achieving a managerial position.Design/methodology/approachThis study is based on research by Cromie. Barriers are classified into two main categories; internal and external barriers. Job‐involvement and work‐based self‐esteem are considered to be internal barriers, whereas attitudes towards women in management are considered to be external barriers. The total population was 200, consisting of male and female middle managers, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 35 publications
3
34
0
Order By: Relevance
“…They indicated that health staff members with low selfesteem also have negative service attitude and low job productivity. Moreover, a significant positive correlation was shown to exist between self-esteem and job involvement (Brown 1996, Cortis & Cassar 2005 and between self-esteem and organisational commitment (Pierce et al 1989). The study by Naderi et al (2009) indicated a significant difference between gender and self-esteem.…”
Section: Discussionmentioning
confidence: 97%
“…They indicated that health staff members with low selfesteem also have negative service attitude and low job productivity. Moreover, a significant positive correlation was shown to exist between self-esteem and job involvement (Brown 1996, Cortis & Cassar 2005 and between self-esteem and organisational commitment (Pierce et al 1989). The study by Naderi et al (2009) indicated a significant difference between gender and self-esteem.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, women managers may need to find their own career paths due the scarcity of women in top leadership, and thus, to the lack of role models as they could not break the glass ceiling. Tlaiss and Kauser (2010) observe that a number of studies have identified organizational barriers that prevent women from advancing such as constraining societal and cultural practices (Benson and Yukongdi, 2006;Wilson, 2003), discriminatory gender-specific factors (Parker and Fagenson, 1994;Powell, 2000), the anti-female nature of organizations (Cortis and Cassar, 2005;Eagly and Carli, 2007;Weir, 2003), and institutional discrimination such as limited access to networking processes, lack of mentoring, and limited training and development opportunities (Cordano et al, 2002;Lahtinen and Wilson, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have categorized the barriers as internal and external (Cortis & Cassar, 2005), or as glass ceiling and glass wall (Powell & Graves, 2003), or as individual, organizational, and societal (Moorosi, 2010).…”
Section: Barriers To Women For Career Progressionmentioning
confidence: 99%